2016
DOI: 10.1115/1.4032123
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Using Augmented Auditory Feedback From a Pressure Detecting Insole to Reduce the Knee Adduction Moment: A Proof of Concept Study

Abstract: The objective of this work was to conduct a proof of concept study utilizing auditory feedback from a pressure-detecting shoe insole to shift plantar pressure medially in order to reduce the knee adduction moment (KAM). When compared with normal walking, 32 healthy subjects significantly reduced their peak KAM using feedback (p < 0.001). When compared with medial thrust gait, an established gait modification, walking with pressure-based feedback was equally effective at reducing the peak KAM, yet it successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In our study we examined the wearable sensing and feedback in a group of young healthy adults, similarly to previous studies evaluating experimental technology for gait retraining [ 7 , 28 , 31 , 32 , 35 , 37 39 , 41 , 42 , 66 ]. However, the eventual application is targeted to patients of KOA who are generally older and less familiar with technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we examined the wearable sensing and feedback in a group of young healthy adults, similarly to previous studies evaluating experimental technology for gait retraining [ 7 , 28 , 31 , 32 , 35 , 37 39 , 41 , 42 , 66 ]. However, the eventual application is targeted to patients of KOA who are generally older and less familiar with technology.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, studies using laboratory-based biofeedback to target knee joint loading either directly or indirectly were analyzed [ 29 ]. Most studies used visual feedback modes [ 7 , 12 , 20 , 30 36 ] or multi-modal visual-tactile [ 37 , 38 ], and less often solely tactile [ 19 , 39 – 41 ] or auditory feedback [ 42 ]. Another review focusing on wearable sensing and feedback techniques reported that until recently, most studies utilizing wearable feedback incorporated primarily tactile modalities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 ). For each frame of data, MLPI was calculated as the perpendicular distance between the centre of pressure (CoP) and the midline of the foot, normalized to the foot width [ 24 ]. Positive and negative values indicate a CoP that is lateral or medial to the midline of the foot, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is also accepted that based on automatically assessed data from sensors, personalized feedback can be generated to help the user in their rehabilitation process [22]. However, there are different conditions and mechanisms that can cause knee pain and particular methods are required for particular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One particular application of insole pressure sensors in the medical and rehabilitation domains is the detection of compensatory walking strategies employed by those with knee pain under different conditions causing the pain. The authors in [22] presented a proof of concept study using augmented auditory feedback from a pressure detecting insole to reduce the knee adduction moment. The work in [23] presents a study focused on the biomechanical implications of knee osteoarthritis (OA) and the association with pain.…”
Section: Related Workmentioning
confidence: 99%